Thrombolytic therapy in older acute ischemic stroke patients with gastrointestinal malignancy or recent bleeding - Inohara, Taku (Eur Stroke J, 2019)
BACKGROUND: There are limited data on the safety of intravenous recombinant tissue plasminogen activator (rtPA) for treating acute ischemic stroke in patients with gastrointestinal malignancy or recent gastrointestinal bleeding within 21 days of their index stroke. AIMS: To evaluate clinical outcomes in patients treated with rtPA for acute ischemic stroke who had gastrointestinal malignancy or recent gastrointestinal bleeding METHODS: We identified patients who were treated with rtPA for acute ischemic stroke between 2/2009 and 12/2015 from the Get With The Guidelines-Stroke linked to Medicare claims data. Gastrointestinal malignancy and recent gastrointestinal bleeding were defined as any gastrointestinal malignancy hospitalisation within one year prior to acute ischemic stroke and gastrointestinal bleeding hospitalisation within 21 days prior to acute ischemic stroke, respectively. Outcomes of interest included in-hospital mortality and bleeding complications. RESULTS: Among 40,396 patients aged 65 years or older treated with rtPA for acute ischemic stroke from 1522 sites (mean age [SD] 81.0 [8.1] years; 41.9% women), 136 (0.3%) had gastrointestinal malignancy (n = 96) or recent gastrointestinal bleeding (n = 43). Patients with gastrointestinal malignancy or bleeding had more severe stroke than those without (median NIHSS [interquartile range]: 14.0 [8.0–19.0] vs. 11.0 [6.0–18.0]). The rates of in-hospital mortality and life-threatening systemic haemorrhage were not significantly different between those with and without gastrointestinal malignancy or bleeding (mortality: 10.3% vs. 9.0%, adjusted odds ratio [aOR] 1.01, 95%CI 0.58–1.75; bleeding: 2.3% vs. 1.2%, aOR 1.72, 95%CI 0.58–5.11). CONCLUSIONS: In this observational cohort, we did not find increased risk of in-hospital mortality and bleeding in rtPA-treated patients with gastrointestinal malignancy or recent gastrointestinal bleeding.